Challenges in the Implementation of Halal Regulations by Local Governments in Supporting the Growth of the Halal Industry: A Case Study of Kudus, Pati, and Jepara Regencies, Central Java. - Muhaimin; Sirajul Munir; M. Rizky Tri Hartono (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
ABSTRACT This study examines the challenges in the implementation of halal regulations by local governments in supporting the growth of the halal industry in the northern coastal region of Central Java, specifically in Kudus, Pati, and Jepara Regencies. Despite having strong potential in agriculture, fisheries, and processed food industries, these regions still exhibit a relatively low number of halal-certified products. If these challenges are not properly identified and systematically addressed, several consequences may arise, including limited access to domestic and international markets, declining consumer trust and product reputation, and constrained opportunities for sustainable halal industry development, potentially widening regional disparities. This research employs a qualitative field research approach to analyze the role of local governments and stakeholders in implementing halal product policies, as well as to identify practical challenges in the field. Data were collected through in-depth interviews, participatory observation, and documentation studies. The findings indicate significant variations in policy implementation across the three regencies, influenced by local regulations, government capacity, inter-agency coordination, and stakeholder participation. Moreover, a substantial gap between the large number of micro, small, and medium enterprises and those that have obtained halal certification reflects limited access to certification services, suboptimal institutional capacity, and weak stakeholder coordination. Additional constraints include the limited number of halal facilitators, complex administrative procedures, and low levels of halal literacy among business actors. These findings highlight the importance of strengthening institutional support, improving coordination, and developing more inclusive and adaptive halal policies to foster a sustainable halal ecosystem.